EMPOWERING INDONESIAN FEMALE DOMESTIC WORKERS - Rosita Tandos (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2014)
Transnational domestic work is a billion dollar business that has a great impact to economic development of both sending and receiving countries. In fact, women are the main actors of this business that involve multiple stakeholders from governmental and non-governmental institutions and private sectors. Realizing the importance position of the women is necessary to enhance policies, programs and services that will bring positive impact to their lives. Islamic community development studies might provide religious perspective that integrates with other disciplines of studies such as social work, public policy and analysis, and social development. It might contribute ideas, principles and values used for improving social and economic conditions of transnational domestic workers. Therefore, it is necessary to extend the concept of Dakwah from communication (dakwah bil-lisan) into creating social action and movement (dakwah bil-hal) for attain extensive social change.***Pekerjaan rumah tangga transnasional adalah bisnis miliar dolar yang memiliki dampak yang besar bagi pembangunan ekonomi kedua negara pengirim dan penerima. Bahkan, perempuan merupakan aktor utama bisnis ini yang melibatkan berbagai pemangku kepentingan dari lembaga pemerintah dan non-pemerintah, dan sektor swasta. Menyadari posisi pentingnya perempuan perlu meningkatkan kebijakan, program dan layanan yang akan membawa dampak positif bagi kehidupan mereka. Studi pengembangan masyarakat Islam dapat memberikan perspektif agama yang terintegrasi dengan disiplin keilmuan lain dari berbagai disilin kelimuan seperti kerja sosial, kebijakan publik dan analisis, dan pembangunan sosial. Pengembangan masyarakat Islam dapat menyumbang-kan ide-ide, prinsip-prinsip dan nilai-nilai yang digunakan untuk meningkatkan kondisi sosial dan ekonomi pekerja domestik-transnasional. Oleh karena itu, perlu untuk memperluas konsep Dakwah dari komunikasi (dakwah bil lisan-) dalam menciptakan aksi sosial dan gerakan (dakwah bil-HAL) untuk mencapai perubahan sosial yang luas.